Advanced Medical Care Program for the Rapid Introduction of Healthcare Technologies to the National Health Insurance System in Japan - Keiko Ueda; Shoji Sanada; Naoto Uemura (Wiley, 2020)
Japan's Advanced Medical Care Program (AMCP) seeks to facilitate patient access to promising healthcare technologies through National Health Insurance (NHI) coverage. This study aimed to examine AMCP's contribution to the accelerated introduction of new technologies through NHI coverage. AMCP‐type B technologies registered May 2006-March 2019 were examined. To investigate the use of AMCP for NHI coverage, data from the AMCP website and from regulatory authority documents were used. Of 127 AMCP‐type B technologies, 38 underwent final review. Fifteen technologies were successfully introduced into NHI coverage. Eight technologies introduced directly through the Advanced Medical Care Conference were related to medical devices. Other technologies, including drugs, required additional accelerated frameworks for market approval. A strategic approach with the careful selection of target therapeutic technologies and accelerated frameworks is key for the rapid introduction of medical technologies through AMCP.